Tingkat Kebisingan Suara di Lingkungan MTS Negeri 34 Jakarta terhadap Kualitas Proses Belajar Mengajar - Septina Severina Lumbantobing; Faradiba Faradiba; Fransiskus Assisi B (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2019)
Schools are places where the teaching and learning process is carried out should provide a conducive atmosphere so that educational goals are expected to be achieved. One of the main factor that is quite disturbing when the learning process takes place is the noise. The school where this research is located is one of the schools that is close to the noise source. The location of this research is 34 MTs in Jakarta which is located at a radius of 0.34 km from the runway of Halim Perdanakusuma airport. This research uses descriptive analysis method. Sound noise level data collection is done by using a sound level meter. Data is measured by a momentary sound pressure level of 5 minutes, or Leq (5 minutes) for each measurement point. The noise level at 34 MTs Jakarta in five measurement points respectively were 84.87 dB, 79.60 dB, 81.73 dB, 81.00 dB and 85.20 dB. The highest noise level is at point 5 which is the side facing the runway at Halim Perdanakusuma airport. The average noise level is 83.85 dB. This value is in the very noisy category according to Kep-48 MNLH / 11/1996. From the results of questionnaire analysis, 46.1% of respondents stated that the school was noisy, then 36.2% of students stated that the noisy conditions disrupted communication while carrying out the learning process in the classroom and 36.9% of respondents stated that noise from Halim Perdanakusuma airport activities disturbed their concentration in the teaching and learning process in the classroom Keywords: noise level, school, sound level meter, learning process